Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s40703-019-0098-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymes on plasticity and strength characteristics of an earthen construction material

Abstract: In this study, a commercially available enzyme which is used popularly to improve sub-grade material for pavements was used as a potential stabilizer to improve soil properties used for earthen construction. As a preliminary study, the interaction of this enzyme with the soil was assessed by evaluating the plasticity and strength characteristics of enzyme treated soil with ageing. From the research findings, it was observed that with ageing, the liquid limit of soil decreased, while plastic and shrinkage limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Thus, there is relatively little literature concerning stabilization mechanisms of bioenzymes in soil stabilization. Two mechanisms of bioenzyme soil stabilization were proposed by researchers [ 44 ].…”
Section: Mechanism Of Bioenzyme Soil Stabilizationmentioning
confidence: 99%
“…Thus, there is relatively little literature concerning stabilization mechanisms of bioenzymes in soil stabilization. Two mechanisms of bioenzyme soil stabilization were proposed by researchers [ 44 ].…”
Section: Mechanism Of Bioenzyme Soil Stabilizationmentioning
confidence: 99%
“…Soil strength improvement is one of the basic requirements of the construction field. Researchers have been making efforts to reduce the dependence on energy-intensive stabilizers such as cement and lime [1]. In this regard several non-traditional stabilizers have been tried for improving desirable soil characteristics, which include sulfonated oils, lignin derivatives, polymer-based additives, resins, enzymes, silicates, and calcium/sodium chloride geopolymers [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Further adding the doubts, enzymes are generally reformulation of other products therefore specific testing for a given enzyme is imperative [13]. Enzymes have actively supported in improving soil health [1,[14][15][16][17][18][19][20] A tropical red soil [1] and compressed stabilized earth blocks [17] were treated with TerraZyme and it was observed that the enzyme improved the compressive strength of the red soil and blocks. Soil (from Tilda region of Chhattisgarh, India) treated with enzyme showed considerable increase in cohesion though marginal increase in angle of internal friction was observed [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations